Education in health with pre-adolescentes from a state school in Fortaleza - CE - Brito, Maria Eliane Maciel; Albuquerque, Jaqueline G.; Silva, Denise A.; Sampaio Filho, Francisco J.L.; Araújo, Flávia V.; Lima, Ivana Cristina V.; Vieira, Neiva F.C.; Pinheiro, Patrícia N.C. (Brazilian Journal of Sexually Transmitted Diseases, 2008)
Introduction: pre-adolescence is characterized by important changes in the life of the youngsters, making them vulnerable to health risks such as: undesirable pregnancy and sexually transmitted diseases. Objective: to experience educational activities with pre-adolescents from a state school; to provide a critical reflection concerning the proper physiological modifications of pre-adolscence and to discuss about prevention control of sexually transmitted disease and aids. Methods: this is a descriptive study, with an active-participation research approach, developed in a prymary School in Fortaleza city, State of Ceará, from March to June, 2007, with adolescents ranging from 9 to 13 years of age. Four educational workshops were used as resources to the study. Bardin (1997) was uded to data analysis. Results: the family does not have the ability to discuss sexual education, violence and harassment among youngnsters are lived inside their own family, in which the “sexuality” is forbiden on dealt with indifference. Students’ responses reinforce that adolescents are starting their sexual life earlier and that unfamiliarity to DST/aids and prevention was common to all subjects in the group. Conclusion: in the end of the workshops it was evidenced that educational strategies with groups of adolescents are implements of great importance to the learning of pre-adolescents, being elements that transform and promote the interaction and growth of the participants. Active pedagogical boardings make construction and reconstruction of knowledges possible, making the individual capable of improving his/he quality of life